Challenges and impacts of the Covid-19 pandemic in Brazil: Perspectives on coping policies and their consequences on public health - Oliveira, Sergio Dionízio de; Barbosa, Roberta Ribeiro Batista; Paiva, Laércio da Silva; Oliveira, Fernando Rocha (Seven Editora, 2023)
The COVID-19 pandemic brought an overload of health systems, with the search for beds to support the demand of patients hospitalized for COVID-19, the heterogeneity and availability of resources in the public and private spheres, was evidenced throughout the pandemic, demonstrating different organizational policies in different regions of Brazil to face the pandemic. To understand the challenges and impacts of the COVID-19 pandemic in Brazil, focusing on the coping policies adopted and their consequences on public health, a literature review was conducted. There was a need to understand the panorama of government actions and their effects on reducing the transmission of the virus, on the response capacity of the health system, and on the social impacts. This review is based on the investigation and analysis of the existing scientific production in the literature, providing a comprehensive compilation of information, covering various topics, allowing the identification of relevant knowledge gaps that can serve as a basis for future research. The country’s economic policy needed to use financial resources to face the crises of the pandemic in the sectors of science, education, health, technology and social protection. This crisis resulting from the pandemic on a global scale also provided a crisis of the sustainable development goals (SDGs), fostering reflections to restore the progress of the SDGs. It is observed that the COVID-19 pandemic has provided negative impacts on the entire world population, stimulating a gap for the reflection of policies to cope with pandemic outbreaks. DOI:https://doi.org/10.56238/sevened2023.004-016